Editorial: Intersectionality and Social Inequalities Beyond Social Origin - Monica Budowski; Andreas Hadjar (sozialpolitik.ch, 2023)
This introductory article to the themed issue on Intersectionality and Social Inequalities Beyond Social Origin highlights some of the debates on social inequality and the historical and theoretical background of intersectionality. It outlines the connections between social inequalites and social policies, e.g., in that social policies aim to reduce social inequalities and improve opportunities and living conditions, yet also produce social inequalities. The article presents the complexities of axes and dimensions of inequalities and how the concept of intersectionality came into play. It discusses the advantages and disadvantages of different approaches to intersectionality. Finally, it introduces the various articles in the issue Socialpolicy 2023(1) that bring together conceptual and methodological issues on intersectionality and exemplify how researchers apply intersectionality in their fields of research, therewith yielding new approaches and novel results for social policy.